Extraction of Shikonin with Surfactant-Assisted Ultrasonic from Arnebia euchroma - Cui, Xiaoqiu (Asian Journal of Chemistry, 2014)
An efficient surfactant assisted ultrasonic extraction technology was employed for extracting shikonin from Arnebia euchroma and the extraction process was optimized. Based on single-factor experiments, a four-factor-three-levels experimental design has been developed. The optimum conditions were carried out at 35 °C for 35 min at a solid-to-liquid ratio of 1:12 upon the addition of 0.0004 g L-1 surfactant. Shikonin contents could be determined readily by high-performance liquid chromatography within 20 min. The mean yield of shikonin was 30.64 mg L-1. Moreover, the contact angle of the powder was 30.501° in methanol. The proposed method was reliable by repeatability, stability and recovery tests. The results indicated that addition of surfactant could significantly increase the extraction yield of shikonin.